Tests of CHS-to-SHS tubular connections in stainless steel. (15th November 2019) - Feng, Ran; Liu, Yuexin; Zhu, Jihua
Highlights: Tests were conducted on CHS-to-SHS tubular T-, Y- and X-connections in stainless steel. Initial stiffnesses and failure strengths increased with the increment of β, and increased with the decrement of θ. Influences of τ and 2 γ on the initial stiffnesses and failure strengths are insignificant. CIDECT and Chinese Code are conservative, and EC3 is most conservative. AS/NZS is generally appropriate for CHS-to-SHS tubular connections in stainless steel. Abstract: A test program was conducted in this study on hybrid tubular T-, Y- and X-connections made of circular hollow section (CHS) braces and square hollow section (SHS) chord in stainless steel. A total of 18 specimens including 4 T-, 5 Y- and 9 X-connections were tested by applying axial compression to the end of circular brace. The failure modes, failure strengths and deformation curves of all specimens were obtained from experimental investigation. The influences of the key geometrical parameters including the brace diameter/chord width ratio ( β ), the brace/chord thickness ratio ( τ ), the chord width/thickness ratio (2 γ ) and the inclined angle ( θ ) between brace and chord on the load-carrying capacities of CHS-to-SHS tubular connections in stainless steel were carefully evaluated. Experimental results show that the initial stiffnesses and the failure strengths of hybrid tubular T-, Y- and X-connections increased with the increment of the β value, and increased with the decrement of the θ value. However, the influences of other geometrical parameters of τ and 2 γ on the initial stiffnesses and the failure strengths are insignificant. Furthermore, the test strengths are compared with the nominal design strengths calculated using the design formulae of the current design specifications including CIDECT, Eurocode 3 (EC3), Australian/New Zealand Standard (AS/NZS) and Chinese Code, in which AS/NZS is the only design guideline for stainless steel structures. The comparison indicates that the design formulae of CIDECT, EC3 and Chinese Code are all conservative, in which the design formulae of EC3 are most conservative with the largest scatter of predictions. While, the design formulae of AS/NZS are generally appropriate for CHS-to-SHS tubular connections in stainless steel.